The location dynamics of knowledge-based service establishments : a Stellenbosch case study - Adendorff, Maria Anita (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2009.